Reliability of peripheral arterial tonometry in patients with heart failure, diabetic nephropathy and arterial hypertension. (August 2017) - Weisrock, Fabian; Fritschka, Max; Beckmann, Sebastian; Litmeier, Simon; Wagner, Josephine; Tahirovic, Elvis; Radenovic, Sara; Zelenak, Christine; Hashemi, Djawid; Busjahn, Andreas; Krahn, Thomas; Pieske, Burkert; et al.
Endothelial dysfunction plays a major role in cardiovascular diseases and pulse amplitude tonometry (PAT) offers a non-invasive way to assess endothelial dysfunction. However, data about the reliability of PAT in cardiovascular patient populations are scarce. Thus, we evaluated the test-retest reliability of PAT using the natural logarithmic transformed reactive hyperaemia index (LnRHI). Our cohort consisted of 91 patients (mean age: 65±9.7 years, 32% female), who were divided into four groups: those with heart failure with preserved ejection fraction (HFpEF) ( n =25), heart failure with reduced ejection fraction (HFrEF) ( n =22), diabetic nephropathy ( n =21), and arterial hypertension ( n =23). All subjects underwent two separate PAT measurements at a median interval of 7 days (range 4–14 days). LnRHI derived by PAT showed good reliability in subjects with diabetic nephropathy (intra-class correlation (ICC) = 0.863) and satisfactory reliability in patients with both HFpEF (ICC = 0.557) and HFrEF (ICC = 0.576). However, in subjects with arterial hypertension, reliability was poor (ICC = 0.125). We demonstrated that PAT is a reliable technique to assess endothelial dysfunction in adults with diabetic nephropathy, HFpEF or HFrEF. However, in subjects with arterial hypertension, we did not find sufficient reliability, which can possibly be attributed to variations in heart rate and the respective time of the assessments.Clinical Trial Registration Identifier: NCT02299960.